Clean and Healthy Living Behavior Management Policy for Early Childhood - Oktafia, Nur Eka; Liftiah, Liftiah; Kusumandari, Rafika Bayu (Dinasti Research, 2025)
The title of this research is “Clean and Healthy Living Behavior Management Policy for Early Childhood”. The objective of this study is to describe and analyze clean and healthy living behavior (PHBS) management policies and practices, including planning, organization, implementation, and evaluation aspects in public and private kindergartens in Semarang City. The approach used is descriptive qualitative, with data collection techniques through in-depth interviews, observation, and documentation. Research informants included principals and teachers from eight purposively selected kindergartens (four public kindergartens and four private kindergartens). The results show that the implementation of PHBS management policies in public kindergartens tends to be structured and refers to formal regulations with an emphasis on habituating healthy behaviors. Meanwhile, private kindergartens develop a more participatory, innovative, and adaptive approach according to the needs of students. Both types of institutions show that the success of PHBS policy implementation is strongly influenced by school leadership, educator involvement, and support from parents and the surrounding environment. These findings emphasize the importance of strengthening contextual, integrated, and sustainable PHBS management policies to optimally form the basis for healthy behaviors in early childhood.